Diagenesis 3. Aspects of the Diagenesis of Coarse-Grained Siliciclastic Rocks - Hutcheon, Ian (Geoscience Canada, 1983)
Summary The process of diagenesis, by which sediments become rock, has many physical and chemical aspects. Even a cursory examination of the scientific literature shows that mineral reactions, original depositional environment, diagenetic environment, the flow of fluid, the evolution of organic matter, the compaction of sediment and the precipitation, replacement and destruction of cements all play a role in sandstone diagenesis. The importance of sandstone diagenesis is evidenced by the rapid increase of pure and applied research in this area. The oil and gas industry has greatly accelerated research into sandstone diagenesis, primarily because the nature and distribution of porosity and permeability ultimately governs the extent of oil and gas recovery, and diagenesis is a controlling factor in the formation and destruction of porosity. In addition, as our demand for oil and gas grows, and the relatively easily extracted oil is exploited, there is an increasing emphasis on secondary and tertiary recovery of conventional oil and recovery of heavy oil and tar sands. Enhanced recovery agents, whether physical (injected water or steam) or chemical (surfactants, acids, polymers, caustic andclay stabilising agents), are in direct contact with the pore space of the rock. It is important to understand the present state of diagenesis of any rock, and how that state will be affected by an agent used to stimulate recovery. While it is tempting to divide the subject of diagenesis into those processes which are physical and those which are chemical, the interdependence of physical and chemical processes makes this impossible. The reader also should be warned that even sandstone diagenesis itself cannot be separated from the interplay of differing sedimentary environments, lithologie variation within basins, and setting and evolution of sedimentary basins. All of these factors are ultimately governed by the tectonic setting.